HARMONIZATION BETWEEN THE NATIONAL AND INTERNATIONAL LAW ON THE USAGE SETTINGS OF NATURAL RESOURCES IN THE TERRITORY OF THE REPUBLIC OF INDONESIA - munsharif abdul chalim (UNISSULA, 2017)
This paper aims to examine the suitability between national law and international law in the regulation of natural resource use. In this paper used the normative juridical method, with primary data contains laws relating directly to international law, while secondary data in the form of journals or library references. The result obtained that Adjustment of the national legal system into a global legal system, it makes positive law becomes harmonious and uniform (harmony of law) and the adjustment of certain legal norms into a unity of global norm which later can be used as a means of dispute resolution. Harmonious and uniform can be achieved if global harmony of decisions are the same. The legal arrangements of the archipelago countries as reflected in the three points raised by the archipelago supporters which reflect the principles of the regime on waters of the archipelago as practiced by Indonesia and the Philippines. In these circumstances the only effort that can be made to unite the opinions in order to get a clear pattern is the consultation with various groups, both between themselves and between groups.